Ten - McNeil, Gretchen (Balzer + Bray, 2013)
When friends Meg and Minnie attend a house party on a nearby island, their good time soon turns sinister when people begin dying and a storm cuts the teens off from the rest of the world. As the death toll mounts, the friends try to find the killer themselves, placing them in a fight for their lives.